Structure and Properties of Dual-doped PEDOT:PSS Multilayer Films - Jucius,Dalius (2019)
Poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is the most successful transparent conductive polymer widely used in functional organic devices. However, its potential in fabrication of highly conductive electrodes still has not been fully explored. This paper is an attempt to fill the existing gap of knowledge on possible post-treatments of dimethyl sulfoxide (DMSO)-doped PEDOT:PSS thin films. In the present study, surface morphology, optical and electrical properties of untreated and sulfuric acid treated DMSO-doped PEDOT:PSS multilayers on the glass coverslip substrates are examined. It is demonstrated that short-time sulfuric acid treatment enhances electrical and optical properties, and smoothens surface of the transparent conductive films. Enhancement of electrical conductivity by more than 30 % can be associated with increase in doping level, removal of excess PSS and accompanied shape alterations of the conjugated PEDOT chains. Acid treatment also results in smoother transmittance spectra and a slight improvement of optical transparency. Hence, sulfuric acid post-treatment can be considered as a simple and inexpensive technique for the complementary doping of DMSO-doped PEDOT:PSS films with the aim to develop the more effective transparent electrodes.